Old comedy and Athenian Power - Lazar, LFSR (Brill Academic Publishers, 2024)
In this article, jumping off from Geoffrey de Ste. Croix’s treatment of Aristophanes and the Megarian Decree, I argue that Old Comedy is an underutilised category of evidence for the study of the popular intellectual history of Athens. My particular focus here is the Athenian empire: how does Old Comedy present Athenian power and what does this comic presentation tell us about how at least some ordinary Athenians understood it? Can one popular Athenian imaginary of the empire be constructed through analysis of Aristophanes and his contemporaries? I will argue that Old Comedy, taken as a corpus, presents a very Athenian empire, that is to say one focused on Athens and its exploitation. The comic poets, therefore, likely assumed parochialism and myopia on the part of their audience, but also significant topical interest in the mechanisms of Athenian power, particularly those which brought revenue to Athens. This impression of highly topical engagement with the empire is corroborated by bringing Comedy into dialogue with other sources, in particular the epigraphic record.